Biodistribution Study of Niosomes in Tumor-Implanted BALB/C Mice Using Scintigraphic Imaging - De Silva, Leanne; Fu, Ju-Yen; Htar, Thet Thet; Wan Kamal, Wan Hamirul Bahrin; Kasbollah, Azahari; Muniyandy, Saravanan; Chuah, Lay-Hong (Frontiers in Pharmacology, 2022)
The purpose of this work was to study the biodistribution of niosomes in tumour-implanted Balb/c mice using Gamma Scintigraphy. Niosomes were formulated and characterized, then radiolabeled with Technetium-99m (99mTc). The biodistribution of 99mTc-labeled niosomes was evaluated in tumor-bearing mice through intravenous injection and imaged with gamma scintigraphy. The labeled complexes possessed high radiolabeling efficiency (98.08 %) and were stable in vitro (>80 % after 8 h). Scintigraphic imaging showed negligible accumulation in the stomach and thyroid, indicating minimal leaching of the radiolabel in vivo. Radioactivity was found mainly in the liver, spleen and kidneys. Tumor-to-muscle ratio indicated a higher specificity of the formulation for the tumor area. The niosomes are stable both in vitro and in vivo, and show preferential tumor accumulation.